Wpływ przejęcia banku na wartość przedsiębiorstwa dla akcjonariuszy - Piecek, Grzegorz (The Effect of Bank Acquisition on Stockholder Wealth, 2007)
For the period 1995 to 2003, the analysis documented significant positive abnormal returns for target banks and insignificant negative abnormal returns for acquiring banks during the announcement Similar studies should be continued in the future, however, to confirm the likelihood that the pattern will continue.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 410-418